STRATEGI PEMASARAN SIRUP MARKISA SINABUNG SEBAGAI PRODUK KEARIFAN LOKAL TANAH KARO - Nataliana Sembiring; Rikawati Ginting Munthe; Eka Pranata Sinulingga (JURNAL REGIONOMIC, 2021)
This study aims to find out the marketing strategy for the local product of Sirup Markisa Sinabung in Karo land which is the business idea of a housewife working who fills time due to the Covid-19 pandemic situation but becomes serious in business development because she sees an open market opportunity to market a product which is a business at home but has an impact on improving the family's economy. The research method uses descriptive qualitative methods and the results of marketing strategy research using marketing mix strategies which are product strategies, pricing strategies, promotion strategies.